Efektifitas Pelaksanaan Program Bantuan Stimulan Perumahan Swadaya (BSPS) di Kecamatan Pantai Cermin Kabupaten Solok - Pangestu, Yangga; Suherman, Hendra; Mulyani, Rini; Carlo, Nasfryzal (Jurnal Talenta Sipil, 2024)
One important step in an effort to meet the housing needs of the community is the construction of housing and settlements whose main goal is to prepare prosperous housing with adequate and affordable infrastructure, facilities and utilities. This study aims to be able to see the extent of the effectiveness of the implementation of the self-help housing stimulant assistance program which refers to technical guidelines. The analysis uses a descriptive qualitative approach, by taking assessment indicators about habitable houses based on technical instructions for the implementation of activities, After that, questionnaires were distributed to 26 houses receiving aid, 14 houses in Nagari Surian and 12 houses in Nagari Lolo Sampling take with using a Likert Scale using a Scale of 5, starting from Very Unsuitable (STS) to Very Suitable (SS), so that the implementation process can run optimally to be able to see threats that occur and also see opportunities to be able to optimize the implementation process is carried out also analysis using the SWOT MethodThe results of the study show that the application of assessment indicators taken from technical implementation guidelines falls into the "appropriate" category where for Nagari Surian it is at 4.14 out of a maximum scale of 5 and for Nagari Lolo it is at 4.16. However, in the aspect of assessing access to adequate tap water in Nagari Lolo is included in the "Quite Appropriate" category, this is because not all houses can be reached by water from Water Suplly Company, so people still rely on tap water from residents' wells or spring sources. The results of the analysis for the value of self-help are also very good because the value of community self-help is 83% - 94%, The role of the facilitator is also very influential on the implementation of the self help housing stimulant assistant program because it can help the community to understand the purpose of the BSPS program itself.